Management of dysphagia in multiple sclerosis: current best practice. (2nd January 2019) - D'Amico, Emanuele; Zanghì, Aurora; Serra, Agostino; Murabito, Paolo; Zappia, Mario; Patti, Francesco; Cocuzza, Salvatore
ABSTRACT: Introduction : Multiple sclerosis (MS) is characterized by extreme variability in both severity and clinical course. It can show severe disabling symptoms, and among them dysphagia is frequently described. However, its management still represents a challenge in the daily care. Areas covered : In this review, we will focus on the clinical recognition and therapeutic strategies to identify and manage dysphagia in people with MS. In the view of a personalized approach, different interventions should be tailored to every single patient. Expert commentary : Multidisciplinary evaluation is mandatory in MS management, and dysphagia represents a perfect model of taking care of a disabling symptom in a chronic disease. Further research is required to better organize a personalized and long-term management of dysphagia phenomenon, through the different subtypes of MS.